Attitudes of Science Teachers toward the use of Participatory Action Research to Solve Problems in an Online Classroom - Yoopandoong, Korawik; Wongwanich, Suwimon; Sriklaub , Kanit (An Online Journal of Education, 2022)
This research aimed to analyze science teachers’ attitudes toward using participatory action research (PAR) along with what caused the teachers to accept and use PAR to solve problems in online classrooms. In the first phase, a 5-rating scale questionnaire about solutions to classroom problems was given to science teachers. The sample included 156 high school science teachers in Thailand obtained through simple random sampling. The instrument underwent quality tests in terms of content validity, reliability, and discrimination, and the results from quality tests used to improve the instrument. In the second phase, 10 selected participants with different backgrounds from the respondents’ questionnaires were interviewed. Descriptive statistics and content analysis were used to analyze the qualitative and quantitative data. The results show that science teachers’ attitudes on using PAR in terms of the intention aspect had a high level of agreement (M = 4.46, SD = 0.53), while the facilitating conditions aspect had the highest level of agreement (M = 4.62, SD = 0.47), and performance expectancy, effort expectancy of PAR use, and social influence in using PAR had a high level of agreement (M = 4.48, SD = 0.54 and M = 4.09, SD = 0.58 and M = 4.13, SD = 0.73), respectively. The interview data shows that teachers intended to use PAR to solve classroom problems since they believed that using PAR will be an effective and clear process, depending on the collaboration of colleagues and a school working system that supports the use of PAR.